Changing trends of gonococcal infection in homosexual men in Edinburgh. - Ross, J. D. (Cambridge University Press, 1991)
In an attempt to explain the recent resurgence of homosexually-acquired gonorrhoea in the Lothian region of Scotland the number of infections and pattern of infection (urethral, rectal and pharyngeal) of all gonococcal isolates from homosexual men attending the Department of Genitourinary Medicine at Edinburgh Royal Infirmary between 1985 and 1990 were analysed. Serovar typing data were available from infections acquired between January 1986 and December 1990. A correlation between one serovar, Bacejk/Brpyust, and the overall pattern of gonorrhoea was observed. The number of infections caused by minor serovars also correlated with rates of gonococcal infection. The number of minor serovars isolated, which may represent strains from other geographical locations, is related to the total incidence of gonorrhoea. It is possible that the incidence of Bacejk/Brpyust may be determined by the size of the infected pool of gonorrhoea. The most likely explanation for the recent increase in gonorrhoea is a change in sexual behaviour and/or an influx of strains from other geographical areas.